CONTAGION EFFECTS OF US FINANCIAL CRISIS ON INDONESIA - Wikanti, Anika Sedyaning (Economic Journal of Emerging Markets, 2011)
This research analyzes the contagion effects of the US financial markets on Indonesian fi-nancial markets during the 2008 global financial crisis. It specifically investigates whether the slump in the US stock prices directly produced a slump in Indonesian stock prices, or indirectly through the slump in regional stock prices. It also examines whether the slump spilled over into rupiah exchange rate. Using Vector Autoregression and Vector Error Correction Model, the paper finds direct contagion effect of the US financial crisis into Indonesian stock markets. It also finds both direct and indirect contagion effect of the US financial crisis into foreign exchange market. Keywords: Contagion, stock price, exchange rate, financial crisis JEL classification numbers: G12, G15